Corn Brownies Making Entrepreneurship Training in The Turi Distric - Wasito Wasito; Dyah Hadi Novida; Ida Fitriani (Indonesian Journal of Cultural and Community Development, 2018)
Community service programs in the form of Entrepreneurship training were carried out in Turi Village, Turirejo Village, Kedamean District, Gesik Regency on August 21, 2017. This activity is the flagship work program of the 2017 KKN management study program. The name of this activity is "Entrepreneurship Training for Making Corn Brownies" with participants PKK mothers and residents of Turi Hamlet. In the training, material with the concept of motivation and entrepreneurship was presented, as well as a cooking demonstration for making corn brownies. The aim of carrying out a work program on entrepreneurship socialization is to provide knowledge to the PKK group of women and Turi hamlet residents about the management and use of local materials such as corn to become entrepreneurial opportunities. Utilization of local potentials owned by the people of Turi hamlet can increase their income with creative capital in managing the agricultural products they have and especially increasing the selling value of corn.